Handover defects: comparison of construction and post-handover housing defects. Issue 3 (2nd April 2016) - Forcada, Nuria; Macarulla, Marcel; Gangolells, Marta; Casals, Miquel
Abstract : Although inspections occur during construction or at handover, customers do not normally participate. This situation creates a gap between the quality perceived by both contractors and customers. An analysis of 52 552 handover defects in 2179 flats in Spain is presented which identified their nature, the building element and trade where these defects are located. These results are compared with previous studies that analysed defects detected during the construction stage and those that remain after handing over the building to the client. The research reveals that structural defects are resolved during construction due to existing quality standards. However, other aesthetic and functional defects remain and/or arise at handover. Some defects are not resolved until customers complain after they first occupy the dwelling. Many functional defects arise due to the lack of involvement of end users in the early project stages.